Impact of daylight saving time on circadian timing system : an expert statement - Meira e Cruz, M. (2019)
Fil: Meira e Cruz, M. Universidad de Lisboa. Facultad de Medicina. Centro Cardiovascular. Unidad de Sueño; Portugal